Supercritical Fluid Chromatography : Volume 1 - Anta, Cristina; Barhate, Chandan L.; Belvo, Matthew; Berger, Terry A.; Burnett, John; Castle, Thomas; Collier, Steven M.; de la Puente, María Luz; Desfontaine, Vincent; Francotte, Eric R.; Guillarme, Davy; Hill, Jason F.; et al. (De Gruyter Textbook, 2018)
Supercritical Fluid Chromatography (SFC) provides a timely overview of SFC application areas which were unimaginable just a decade ago. This two-volume series opens with an overview of the history and expectant future of SFC and continues with recent applications in the pharmaceutical industry and other fascinating areas of science. SFC has found its place in the pharmaceutical industry with an increasing body of applications for chiral and achiral molecules in both the research and development phases of the drug discovery process. As illustrated in this two-volume series, the current interest in SFC extends well beyond the pharmaceutical industry. Chapters encompassing applications for polar and non-polar mixtures of importance are covering widely disparate areas in substance abuse, natural products including cannabinoids, bioactive lipids, flavor and fragrance. With its broad balance and coverage, this two-volume book constitutes a unique educational platform to students and scientists for many years to come. The major objective of this book editions is to inspire and stimulate readers to continue exploring the possibilities of exploiting supercritical fluids as a particular media for analysis, purifications and synthesis.